2009
DOI: 10.1103/physrevd.79.044012
|View full text |Cite
|
Sign up to set email alerts
|

Lovelock black holes with a nonlinear Maxwell field

Abstract: We derive electrically charged black hole solutions of the Einstein-Gauss-Bonnet equations with a nonlinear electrodynamics source in n(≥ 5) dimensions. The spacetimes are given as a warped product M 2 × K n−2 , where K n−2 is a (n − 2)-dimensional constant curvature space. We establish a generalized Birkhoff's theorem by showing that it is the unique electrically charged solution with this isometry and for which the orbit of the warp factor on K n−2 is non-null. An extension of the analysis for full Lovelock … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
151
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 125 publications
2
151
0
1
Order By: Relevance
“…The Bardeen black holes are also generalized to the model with four specific parameters [22]. Recently, a large class of black hole solutions have been constructed in the power Maxwell theory [23][24][25][26] in which the Maxwell action takes as power-law function of the form L = −β(F µν F µν ) k , where β is a coupling constant and k is a power parameter. It is found that the asymptotic behavior of the solution depends heavily on the value of the power parameter k. Moreover, the black hole solution have been considered in the modified Maxwell field including the nonminimal coupling between the gravitational and electromagnetic fields [27].…”
Section: Introductionmentioning
confidence: 99%
“…The Bardeen black holes are also generalized to the model with four specific parameters [22]. Recently, a large class of black hole solutions have been constructed in the power Maxwell theory [23][24][25][26] in which the Maxwell action takes as power-law function of the form L = −β(F µν F µν ) k , where β is a coupling constant and k is a power parameter. It is found that the asymptotic behavior of the solution depends heavily on the value of the power parameter k. Moreover, the black hole solution have been considered in the modified Maxwell field including the nonminimal coupling between the gravitational and electromagnetic fields [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since Heisenberg and Euler [23] noted that quantum electrodynamics predicts that the electromagnetic field behaves nonlinearly through the presence of virtual charged particles, the nonlinear electrodynamics has been an interesting subject for many years [24][25][26][27][28][29][30][31][32] because the nonlinear electrodynamics carries more information than the Maxwell field. One of the important nonlinear electrodynamics is the logarithmic electromagnetic field which appears in the description of vacuum polarization effects.…”
Section: Introductionmentioning
confidence: 99%
“…One of the special classes of nonlinear electrodynamics is Power Maxwell Invariant (PMI) theory [38,53,54,55,56,57,58,59,60]. The PMI theory has an interesting result which distinguishes this nonlinear theory from others; this theory enjoys conformal invariancy when the power of Maxwell invariant is a quarter of spacetime dimensions (power = dimensions/4).…”
Section: Power Maxwell Invariant (Pmi) Sourcementioning
confidence: 99%
“…It is worth mentioning that the idea is to take advantages of the conformal symmetry to construct the analogues of the 4 dimensional Reissner-Nordström solutions with an inverse square law for the electric field of the point-like charges in arbitrary dimensions. Now, we take into account the Lagrangian of nonlinear PMI model with the following explicit form [38,53,54,55,56,57,58,59,60] L…”
Section: Power Maxwell Invariant (Pmi) Sourcementioning
confidence: 99%